Effect of Aloe barbadense Leaf and Gel Aqueous Extracts During the Starter and Finishing Phases of Broiler Production - Bernard, N.; Mohammed , A.; Edwards, A.; Bridgemohan, P. (International Journal of Poultry Science, 2015)
Leaf and gel extracts of Aloe barbadense are added to the drinking water in local broiler production to reduce mortality and enhance broiler performance. In this study, 420 day-old chicks (Aber Acres) were randomly divided into 7 groups of 60 chicks of mixed sexes of 20 per replicate (3 replicates per group). The experiment used a 2 x 3 x 3 randomized design with three experimental treatments of either Aloe vera (Aloe barbadense) gel T1, T2, T3, or leaf (T4, T5, or T6) and one control. Across the 42-day grow-out period, there were no significant differences (p>0.05) in feed intake (FI), water consumption (WI), average daily gain (ADG), or feed-conversion ratios (FCR) across treatments. At the end of 21 days, however, the lowest FCR indicator of best performance was found in the T6 20 mL-treated leaf extract group. However, both the 20 mL leaf and 15 mL gel extracts were likely to produce birds of similar weights as traditionally formulated feeds for broilers. Therefore, poultry producers should include a moderate level of Aloe vera gel and the highest leaf extracts in the drinking water, as these extracts may prove to be more cost effective than manufactured feeds for optimal broiler performance. It may also be more cost effective for the poultry producer to use the 20 mL leaf and gel extracts as a means of reducing overall mortality. The finding that compounds in Aloe vera foster less bone deposition and greater muscle accretion in female broilers warrants further investigation.